Electric field determination in the plasma-antenna boundary of a lower-hybrid wave launcher in Tore Supra through dynamic Stark-effect spectroscopy. (22nd April 2015) - Martin, E H; Goniche, M; Klepper, C C; Hillairet, J; Isler, R C; Bottereau, C; Colas, L; Ekedahl, A; Panayotis, S; Pegourie, B; Lotte, Ph; Colledani, G; et al.
Abstract: Interaction of radio-frequency (RF) waves with the plasma in the near-field of a high-power wave launcher is now seen to be an important topic, both in understanding the channeling of these waves through the plasma boundary and in avoiding power losses in the edge. In a recent Letter, a direct non-intrusive measurement of a near antenna RF electric field in the range of lower hybrid (LH) frequencies ( E LH ) was announced (2013 Phys. Rev. Lett. 110 215005). This measurement was achieved through the fitting of Balmer series deuterium spectral lines utilizing a time dependent (dynamic) Stark effect model. In this article, the analysis of the spectral data is discussed in detail and applied to a larger range of measurements and the accuracy and limitations of the experimental technique are investigated. It was found through an analysis of numerous Tore Supra discharges that good quantitative agreement exists between the measured and full-wave modeled E LH when the launched power exceeds 0.5 MW. For low power the measurement becomes inaccurate utilizing the implemented passive spectroscopic technique because the spectral noise overwhelms the effect of the RF electric field on the line profile. Additionally, effects of the ponderomotive force are suspected at sufficiently high power.